Promotional activities of Scientific and Technological Information (STI) Services in Indonesia and the Philippines a comparative study - Kadir, Abdul; Sison, Josephine C.; Vallejo, Rosa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
This study was designed to identify the techniques and methods of promotional activities of STI services and products in Indonesia and the Philippines, and to compare the level of activity in each country. The administration and management aspect of the promotional activities was also investigated to give a comprehensive view of the activities.
This study was based on a survey questionnaire which was distributed to fifteen libraries in Indonesia under the science and technology library consortium which is coordinated by PDIN-LIPI (Pusat Dokumentasi Ilmiah Nasional-Lembaga Ilmu Pengetahuan Indonesia or National Scientific Documentation Center-Indonesian Institute of Sciences), and in the Philippines, fourteen libraries in institutions under and or attached to the NSTA (National Science and Technology Authority). Because one library was newly organized and another uses the facilities and resources of another library which is a respondent in this study, only the data from twenty-seven libraries were eventually included, and were analyzed, tabulated, and interpreted. The promotional activity score was used to facilitate comparison and analysis. The median test, the Fisher exact probability test, and the chi-square test were used to test the hypotheses.
The survey was undertaken in Indonesia by a research assistant, who distributed and collected the questionnaires sent by this researcher, and in the Philippines by the researcher himself during the period November 1983 to January 1984.
The major findings of the study are that 73 percent of Indonesian libraries use brochures/flyers, direct mail, and personal visits/contacts as promotional methods of their STI services and products, whereas Philippines libraries use brochures/flyers (92 percent), direct mail and sponsored activities (83 percent), and press releases (75 percent). The majority of Indonesian libraries (67 percent) use the house journal as medium of promotion, but Philippine libraries use more varied media, i.e., local press (83 percent), house journal (75 percent), and audiovisual presentation (83 percent). In Philippine libraries using brochures/flyers was the most effective technique according to 58 percent of the respondents, while in Indonesian libraries, brochures/flyers and personal visits/contacts were the most effective technique of promotional activities, according to 26.67 percent of the respondents.
The respondents from both countries, Indonesia and the Philippines, said they conducted user studies through questionnaires, with 73 percent and 75 percent of Indonesian and Philippine libraries responding, respectively. However, less than half of all the libraries in both countries have a planned annual program of promotional activities. More than half of all the libraries in both countries have units or persons within the organization responsible for promotional activities. With regards to the budget available for promotional activities, the libraries in both countries have only a median percentage of 6.25 percent from the total library budget.
Eighty-five percent of libraries in Indonesia and the Philippines reported that promotional activities did affect the use of existing STI services and products.
Even though there was a slight difference in the promotional activites score between Indonesian and Philippine libraries, with the use of statistical tests this difference was proven to be not significant.
The study recommends that promotional activites should be improved and expanded to reach more users and potential users. More tools, methods and techniques of promotional activites should be used, to make potential users aware of STI services and products available in both countries, Indonesia and the Philippines. The press and particularly the local press can play an important part in a library's promotional activites. The librarian should seek press cooperation. Like the press, radio also provides the librarian with an outlet for promotional activities materials. From voice and vision to paper and print. Library publications are an integral part of a promotional activities programme. The sales literature of the library's publication ranges from glossy prestige brochures to one-sheet duplicated booklists. Tape-slide productions are another way of promoting the library; video equipment might also be used. An audience for library promotion may also be found at exhibitions. The library should seek out opportunities to put its messages across at trade shows, country fairs, and careers conventions. If a library is to be professionally engaged in promotional activities work, then staff and time must be made available. Staff must be trained in promotional activites, and made aware of the financial implications of the activites.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Indonesian National Scientific Documentation Center--Information services; Information services--Indonesia.; Information services--Philippines.; Philippines. National Science and Technology Authority--Information services